The Sensitivity of the CPI to Exchange Rates: Distribution Margins, Imported Inputs, and Trade Exposure - Goldberg, Linda S; Campa, José Manuel (The Review of Economics and Statistics, 2010)
This paper quantifies the relative importance of the different channels of CPI responsiveness to exchange rates and import prices across 21 industrialized economies. The paper provides new and rich cross-country and cross-industry details on the sensitivity to exchange rates of distribution margins; the extent of imported inputs use in different categories of consumption goods; and on their role in consumption of nontradables, home-produced tradables, and imported goods. The dominant channel for CPI sensitivity is through the costs arising from imported input use in goods production. This channel is more important than changes in prices of imported goods directly consumed.